Reconciling Environment and Development: Legal Transformation in the Job Creation Law Through a Green Constitution - Elfudllatsani , Bahar (Academos, 2024)
This research examines the compatibility of the Job Creation Law with the principles of the green constitution in the context of environmental protection and people's constitutional rights. The Job Creation Law was born to accelerate investment and simplify regulations. This raises concerns about the potential decline in environmental quality. This research uses a normative legal approach and literature analysis to identify the impact of the Job Creation Law on the environment and its integration with the green constitution. The discussion shows that the Job Creation Law tends to neglect environmental protection, reducing the role of state oversight and public participation. The results of this study emphasize the need for policy revision to integrate the principle of environmental sustainability in the legal framework of economic development. Public participation is also key to the success of sustainable environmental protection. This is because the people who will be directly affected by environmental changes are the people. Policy development that integrates sustainable principles in all aspects of economic development without sacrificing the environment. Keywords: Environmental Protection; Green Constitution; Job Creation Law; Sustainable Development.